Autoimmune Polyendocrine Syndrome 3 Onset with Severe Ketoacidosis in a 74-Year-Old Woman. (2nd March 2015) - Benedini, Stefano; Tufano, Antonietta; Passeri, Elena; Mendola, Marco; Luzi, Livio; Corbetta, Sabrina
Abstract : Type 1 diabetes mellitus (T1D), autoimmune thyroid disease, and autoimmune gastritis often occur together forming the so-called autoimmune polyendocrine syndrome type 3 (APS3). We here report a clinical case of a 74-year-old woman who presented for the first time with severe hyperglycemia and ketoacidosis diagnosed as T1D. Further clinical investigations revealed concomitant severe hypothyroidism with autoimmune thyroid disease and severe cobalamin deficiency due to chronic atrophic gastritis. The diagnosis of type 1 diabetes mellitus was confirmed by the detection of autoantibodies against glutamic acid decarboxylase 65, islet cell antibodies, and anti-insulin autoantibodies. Anti-thyroperoxidase, anti-thyroglobulin, and anti-gastric parietal cell antibodies were also clearly positive. The case emphasized that new onset diabetic ketoacidosis, hypothyroidism, and cobalamin deficiency may simultaneously occur, and one disease can mask the features of the other, thereby making diagnosis difficult. It is noteworthy that an APS3 acute episode occurred in an asymptomatic elder woman for any autoimmune diseases.